Utilization of Bing Image Creator to Design Learning Media with the Theme of Natural Disasters in the Form of Artificial Intelligence-Based Animation - Yamres Pakniany; Latue, Philia Christi; Heinrich Rakusa (Yayasan Perguruan Kampus, 2023)
This research describes the utilization of the Bing Image Creator platform in designing learning media with the theme of natural disasters in the form of animations supported by Artificial Intelligence (AI). Increasingly sophisticated AI technology has brought significant innovation in education, and in the context of natural disaster learning, it opens the door for educators to create more engaging, informative and adaptive learning experiences. Bing Image Creator provides access to a variety of high-quality images and illustrations that allow curriculum creators to depict in detail the phenomenon of natural disasters. This research uses a descriptive qualitative approach. This research uses the Bing Image Creator platform to design learning media with the theme of natural disasters in the form of animation. The results showed that the integration of AI Bing Image Creator really helped the teacher to design learning media with the theme of natural disasters in the form of animations which included floods, landslides, volcanic eruptions, tsunamis, putting winds, tsunamis and earthquakes to help in the teaching and learning process. Another result is a learning media that allows students to better understand the causes, impacts and coping tactics of natural disasters, as well as increase awareness and preparedness in facing disaster threats. This article discusses the concepts and implications of using Bing Image Creator and AI in the context of natural disaster education and its impact on learning effectiveness and student understanding.